Pcr assay and microscopy for examination of mixed ehrlichia canis and babesia spp. infection in bomb-sniffing dogs and other canines in national capital region, philippines - Abigail M. Baticados; Waren N. Baticados; Lorelie A. Villarba; Enrique T. Carlos; Sixto M. E.A.S. Carlos; Paul Vincent Fajardo (Eurasian Journal of Veterinary Sciences)
Aim: There are yet no published records detailing molecular identification of Babesia and Ehrlichia species in dogs in the Philippines. The detection of mixed Ehrlichia canis and Babesia spp. infection in canines of selected municipalities of the National Capital Region (Metropolitan Manila) using PCR was therefore endeavored. In addition, the research further intended to detect the individual organisms in different municipalities, age and sex categories as well as between groups of mixed and pure breed dogs. Materials and Methods: A total of 168 canine blood samples from selected municipalities of Metropolitan Manila were examined for E. canis and Babesia spp. infection using blood parasite examination (BPE) and polymerase chain reaction (PCR) assay methods. Results: All the blood samples subjected to BPE and PCR assay were found negative for E. canis and Babesia spp. The data showed that in terms of the different parameters there were more females (60.11%); purebred (88.10%) and dogs aged <1-2 years (32.94%). Conclusion: Negative results do not automatically dictate the absence of the pathogens. This is because false-negative results may occur in the following conditions; during sub-detectable quantities of pathogens in the blood due to localization of the pathogen in other organs of the body, stages of chronic and asymptomatic carriers of infection; timing of collection; ongoing or past treatments administered and presence of other diseases.